Caracterização potenciométrica de substâncias húmicas extraídas de solos da Antártica Marítima - Carvalho, Juliana Vanir de Souza; Mendonça, Eduardo de Sá; La Scala Júnior, Newton [UNESP]; Reis, César; Reis, Efrain Lázaro; Schaefer, Carlos Ernesto G. R. (Sociedade Brasileira de Química, 2013)
Monitoring of soil carbon storage may indicate possible effects of climate change on the terrestrial environment and it is therefore necessary to understand the influence of redox potential and chemical characteristics of humic substances (HS) of Antarctic soil. Five soils from King George Island were used. HS were extracted, quantified and characterized by potentiometry and the content of total carbon and nitrogen determined. HS of these soils had greater aliphatic character, low content of phenolic groups, lower acidity and lower formal standard electrode potential, compared to HS of soils from other regions, suggesting they are more likely to be oxidized.
Potentiometric characterization of humic substances extracted from Antarctic Marine soils
Keywords: redox titrations; redox potencial; C-CO2 emission